(untitled) (The International Journal for Scientific Research, 2025)
In light of the rapid digital transformation in the banking sector, this study aimed to measure and analyse the level of customer satisfaction with mobile banking applications in Sudan by examining the impact of several technical and service-related factors, including: usability, security and privacy, quality of banking services and modern technologies, technical stability, and customer support. The research problem derivates from the observed variation in user satisfaction despite the growing adoption of digital platforms by Sudanese banks. The study utilized a descriptive analytical quantitative approach and collected data using a structured questionnaire distributed to a random sample of 277 active users. The instrument was developed based on established theoretical frameworks, specifically the SERVQUAL and Technology Acceptance Model (TAM). The results revealed that usability and interface design were the most influential factors on customer satisfaction, followed by service quality, then system stability and technical support, while the effect of security and privacy was relatively limited. The overall customer satisfaction level was found to be statistically high (mean = 3.89 out of 5), and the regression model explained 68% of the variance in satisfaction (R² = 0.677). The study recommends adopting user-centered design approaches, investing in digital infrastructure, improving technical support, enhancing security systems, and introducing innovative digital banking services, in order to strengthen customer loyalty and support sustainable digital transformation and financial inclusion in the Sudanese banking sector.